Learning Organizational Leadership Strategy in Improving the Quality of Middle Level Education - Muhammad Ihsan Dacholfany; Samsudin Samsudin; Rinovian Rais; Ferdinand Salomo Leuwol; Hasyim Mahmud Wantu (Edumaspul: Jurnal Pendidikan, 2023)
The research is motivated by the need to form an appropriate leadership strategy to improve the quality of education by collaborating with all members including teachers, staff, students, and parents or guardians of students. This study aims to analyze and answer learning organization leadership strategies in improving the quality of secondary education. The research method used is a literature study based on articles, papers, books and other sources that support research with a qualitative approach. The results of this study indicate that improving the quality of secondary education requires strong leadership from school principals, good teacher performance, student and parent involvement in the education process, and attention to internal and external factors that affect education quality.